ANALYSIS OF MEANS OF IMITATION MODELING USED FOR THE STUDY OF MANAGEMENT PROCESSES IN MEDICAL INSTITUTIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The article considers the common media of event and multiparadigmatic modelling, as applied to the modelling of the processes of medical institutions to serve the public. The possibilities of managing these processes and optimizing the use of available resources are considered. Formulated recommendations on the use of computer environments in the analysis of business processes and processes of care for the population.